Collateral damage: necroptosis in the development of lung injury - Faust, Hilary (Am J Physiol Lung Cell Mol Physiol, 2020)
Cell death is increasingly recognized as a driving factor in the development of acute lung injury. Necroptosis, an immunogenic regulated cell death program important in innate immunity, has been implicated in the development of lung injury in a diverse range of conditions. Characterized by lytic cell death and consequent extracellular release of endogenous inflammatory mediators, necroptosis can be both beneficial and deleterious to the host, depending on the context. Here, we review recent investigations linking necroptosis and the development of experimental lung injury. We assess the consequences of necroptosis during bacterial pneumonia, viral infection, sepsis, and sterile injury, highlighting increasing evidence from in vitro studies, animal models, and clinical studies that implicates necroptosis in the pathogenesis of ARDS. Lastly, we highlight current challenges in translating laboratory findings to the bedside.